To Control Mobile Web Services Access Using Fuzzy Logic - Wagh, KS (International Journal of Computer Sciences and Engineering, 2019)
Now a day’s mobile computing is becoming very popular and web services are new forms of software platform having standard protocols. Web services can be universally deployed and invoked using specified protocols. Implementing web service on Smartphone’s is a tedious process because of several physical restrictions in Smartphone’s. Smartphone’s are physically constrained devices with different operating systems like Android, iOS, blackberry, Symbian and many others. Physical constraints in Smartphone’s are limited memory, low processing power, intermitted wireless connection and limited battery. This factor needs to be considered while implementing web services for mobile devices. In this paper, we evaluate the RESTful web service for Smartphone’s. When picking a service to execute business logic transactions efficiently, we need to consider availability, accessibility, response time, and scalability as quality attributes. While taking into consideration of physical constraints of mobile devices we implement a controlled web service using fuzzy logic.